(untitled) (Al-Qamar, 2021)
Na ̒t is considered as the most sacred tribute of a poet to Prophet Mohammad and thus involves an emotional attachment rather than a critical approach, yet as to the extent of Noor-ul-Hassan Noor Nawabi Azizi’s Na̒tiya poetry, it encapsulates marvelous tradition of novel subjects on the character, mental and physical behavior of the Holy Prophet. This article tends to explore the variety of subjects in a more to the point approach. Noor’s Na ̒t comprise over a wonderful array of character objectivity.